Knowledge, attitudes, and anxiety of midwives toward maternal care during the COVID-19 pandemic: A descriptive study on midwives who experience the perinatal and breastfeeding phases - Ocktariyana; Dian Lestari (Wolters Kluwer Medknow Publications, 2023)
Background: People all over the world, including pregnant women, have experienced stress and anxiety due to the coronavirus disease 2019 (COVID-19) pandemic. Providing services during the pandemic is something that midwives in primary health care cannot avoid. This study assesses a midwife's knowledge, attitude, and anxiety toward providing maternal care during the pandemic. Material and Method: A cross-sectional design was used in this study, which involved 183 midwives who provided midwifery services at hospitals and health centers and had experience with the perinatal and breastfeeding phases. Using the Google Forms tool, respondents completed a questionnaire regarding their knowledge, attitudes, and anxiety toward maternal care during the COVID-19 pandemic. Results: One hundred eighty-two midwives (99.50%) understood maternal care well during the COVID-19 pandemic. In addition, the maternal care provided during the COVID-19 pandemic was viewed favorably by almost all the participants. The percentage of midwives working in primary care in the perinatal phase who had moderate-to-severe anxiety levels during the COVID-19 pandemic was 17 women (27.42%). Conclusions: The knowledge and attitudes of midwives about the COVID-19 pandemic in this study were good, and there was a smaller percentage of midwives with an extreme level of anxiety.